2000
DOI: 10.1159/000026255
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alzheimer’s Disease and Other Dementing Disorders in an Urban Community of Beijing, China

Abstract: A door-to-door two-phase study was used to investigate the prevalence of senile dementia in an urban community of Beijing. In the study population, 5,003 individuals aged 60 years and older (≥65 years, n = 3,728) were screened at home with the Chinese version of the MMSE. Persons who screened positive for dementia, using different cutoff scores based on degree of literacy, were further evaluated using the criteria of DSM-III-R and ICD-10. Among subjects who screened positive in phase I, 134 were diagnosed as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 20 publications
(37 reference statements)
1
28
0
Order By: Relevance
“…A comparison of worldwide epidemiological studies shows that both the incidence and prevalence gures for dementia increase with age and that women have a higher risk for developing AD according to every report available in the literature (7,46,74,101). There are also signi cant differences in incidence and prevalence around the world (74,101,110). The increased risk of AD, as well as PD, with lower literacy (50,90) could be related to exposure to toxins and PM in the environment, starting in childhood, and occupational history involving exposure to iron, copper, manganese, mercury, zinc, and lead (51).…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of worldwide epidemiological studies shows that both the incidence and prevalence gures for dementia increase with age and that women have a higher risk for developing AD according to every report available in the literature (7,46,74,101). There are also signi cant differences in incidence and prevalence around the world (74,101,110). The increased risk of AD, as well as PD, with lower literacy (50,90) could be related to exposure to toxins and PM in the environment, starting in childhood, and occupational history involving exposure to iron, copper, manganese, mercury, zinc, and lead (51).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The point prevalence of vascular dementia in mainland China ranges from 0.17% to 1.37%. 6,7 The point prevalence of vascular dementia in Hong Kong is 1.79%. 8 There has been a recent upsurge of interest in poststroke dementia (PSDE), which is a subtype of vascular dementia.…”
mentioning
confidence: 99%
“…5 Different studies in Asia showed the prevalence of dementia among the persons aged 65 years and above were in between 2.4% to 3.5%. [6][7][8] According to World Health Organization (WHO), dementia has emerged as a public health priority because it causes the devastating economic burden on families and nations. The cost of dementia will rise at a greater rate than the prevalence.…”
Section: Introductionmentioning
confidence: 99%